An efficient link aware route selection algorithm for WiMAX mobile multi-hop relay networks - Satiman, Nurulashikin (Foundation of Computer Science, 2011)
Multi-hop relay technology is designed to provide capacity enhancement and coverage extension for wireless broadband access system such as WiMAX and LTE-Advanced. However, overall system performances worsen as the number of hop increases. For this reason, resource control function specifically route selection problem should be tackled precisely so that better system performance can be achieved. Route selection or routing is a process to identify the best route to deliver information from source to destination by considering the constraints of available radio resource of the route. In this paper, we proposed a new route selection scheme named as Link Aware Route Selection Scheme (LARSS) for WiMAX Mobile Multi-hop Relay Networks aiming at maximizing network throughput and minimizing end-to-end delay. The proposed scheme exploits link quality and hop count as route metric. We conducted simulation study to evaluate the performance of the proposed scheme. Through the simulation, our proposed scheme outperformed the existing scheme in term of throughput and end-to-end delay.